Effectiveness of Law Enforcement Against Violations of Fiduciary Agreements in Indonesia - Polontoh, Herry; Hartini, Sri Iin (Jurnal Hukum dan Keadilan, 2024)
Law enforcement against violations of fiduciary agreements in Indonesia is an important concern because of the frequent violations that harm the parties involved. Fiduciary agreements that should provide legal certainty are often not implemented properly due to various obstacles in the law enforcement system. This research aims to analyze the effectiveness of law enforcement against breaches of fiduciary agreements in Indonesia, identify challenges faced, and propose strategic steps to improve the effectiveness of law enforcement. This research uses a qualitative method with a normative legal approach. The results show that law enforcement against breach of fiduciary agreement in Indonesia still faces various challenges, such as lack of legal awareness among the public, complicated administrative procedures, lack of coordination between institutions, and limited resources in law enforcement agencies. There are several strategic steps that can be taken to improve the effectiveness of law enforcement, including increased legal socialization and education, simplification of procedures, strengthening of inter-agency coordination, and capacity building of law enforcement agencies through training and technology. By implementing the proposed measures, it is expected that fiduciary law enforcement in Indonesia can become more effective, provide better legal protection, and increase public confidence in the legal system.